2021
DOI: 10.1101/2021.08.20.456971
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extracellular Vesicles Facilitate Large-Scale, Homogenizing Dynamic Exchange of Proteins and RNA Among Cultured Chinese Hamster Ovary (CHO) and Human Cells

Abstract: Cells in culture are viewed as unique individuals in a large population communicating through extracellular molecules and, more recently extracellular vesicles (EVs). Our data here paints a different picture: the homogenizing effect of large-scale exchange of cellular material through EVs. We show that Chinese Hamster Ovary (CHO) cells dynamically produce and uptake EVs, to exchange proteins and RNAs at large-scale. To visualize the dynamic production and cellular uptake of EVs, we used correlative confocal mi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 35 publications
(72 reference statements)
0
0
0
Order By: Relevance
“…CHO EVs have only recently garnered significant attention. In particular, we have found that CHO EVs exchange large quantities of RNA cargo between their parent cells (Belliveau & Papoutsakis, 2022. The nature of that cargo, which has been investigated by several groups (Belliveau & Papoutsakis, 2023;Busch et al, 2022;Keysberg et al, 2021), is now known to vary significantly as a function of metabolite (ammonia and osmotic) stress (Belliveau & Papoutsakis, 2023).…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…CHO EVs have only recently garnered significant attention. In particular, we have found that CHO EVs exchange large quantities of RNA cargo between their parent cells (Belliveau & Papoutsakis, 2022. The nature of that cargo, which has been investigated by several groups (Belliveau & Papoutsakis, 2023;Busch et al, 2022;Keysberg et al, 2021), is now known to vary significantly as a function of metabolite (ammonia and osmotic) stress (Belliveau & Papoutsakis, 2023).…”
Section: Introductionmentioning
confidence: 89%
“…CHO cells were obtained and cultured as described previously (Belliveau & Papoutsakis, 2022. Briefly, a CHO-K1 cell line expressing the VRC01 antibody was cultured in HyClone ActiPro media (Cytiva, Marlborough, MA, USA) supplemented with 6 mM L-glutamine.…”
Section: Cho Cell Culturementioning
confidence: 99%
See 3 more Smart Citations